Shear-enhanced membrane filtration of model and real microalgae extracts for lipids recovery in biorefinery context. (September 2019) - Villafaña-López, Liliana; Clavijo Rivera, Erika; Liu, Shuli; Couallier, Estelle; Frappart, Matthieu
Graphical abstract: Highlights: Rotating disk (RD) filtration is promising for microalgae extracts fractionation. After membrane selection, RD and cross-flow filtration were compared. RD filtration presented higher permeate flux when filtering a model solution. RD filtration performance increased when using real microalgae products. Lipid concentration and coalescence occur at adequate shear rate and TMP. Abstract: In this work, the hydrodynamic effects of rotating disk filtration (with maximum shear rates of 16, 000 s −1 and 66, 000 s −1 ) were evaluated and compared with the crossflow filtration (16, 000 s −1 ) in the recovery of lipids from a model solution that simulates the characteristics of Parachlorella kessleri aqueous extracts. Four polymeric membranes were tested. The PAN 500 kDa membrane along with the rotating disk filtration presented the best performances for lipid concentration and coalescence. The rotating disk filtration was tested with real microalgae extracts, confirming the total lipid retention and the limited membrane fouling.